Program 3 T (Tahaffudz, Ta’allum, and Ta’ammul) Sebagai Internalisasi Konsep Haqqa Tilawatih: Study di Pondok Yanbu’ul Qur’an Remaja Kudus - Istianah, Istianah; Mahtida, Khusna (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2021)
This article examines the 3T program (Tahaffudz, Ta'allum, and Ta'ammul) as an internalization of the concept of haqqa tilawatih in (QS al-Baqarah [2]: 121) study at Pondok Tahfidz Yanbu'ul Qur'an Youth in Kudus. The Islamic boarding school is a forum for educating and guiding the character of students. In an effort to shape the character of the students, the right rules are made in training character learning that is responsive in facing problems in life. This research used a qualitative descriptive method, namely Filled Research (field research) with a study of living Qur'an research. The purpose of this research is to prove the existence of the Brand Image of PTYQR (Pondok Tahfidz Yanbu'ul Qur'an Youth) as a benchmark for all Islamic boarding schools in Tahfidz al-Qur'an. The results of this research prove that the 3T program, namely Tahaffudz, Ta'allum, and Ta'ammul (memorizing, studying, and practicing) as an internalization of the concept of haqqa tilawatih (QS. Al-Baqarah [2]: 21) is very influential for the students. regeneration of the Qur'anic Expert. It is proven that Pondok Tahfidz Yanbu'ul Qur'an has succeeded in giving birth to a generation that excels in memorizing the al-Qur'an and has a good character as well as having social sensitivity.